IMPLEMENTASI KEBIJAKAN KEPARIWISATAAN DI OBJEK WISATA AIR TERJUN SEMIRANG, DUSUN GINTUNGAN, DESA GOGIK, KABUPATEN SEMARANG - Aulia Rafi Al Kautsar; Nina Widowati; Maesaroh Maesaroh (Journal of Public Policy and Management Review, 2022)
Tourism plays an important role in promoting local development and generating revenue for local governments.The government of Semarang district, to promote the tourism sector, made a tourism policy in Regional Regulation No. 8 of 2019 on the Master Plan of Tourism Development for Semarang District in the years 2020–2025. One of the tourist destinations mentioned in Regional Regulation No. 8 of 2019 for Semarang District is the Semirang Waterfall tourist destination, located in Gintungan Hamlet, Gogik Village, Semarang District. However, based on the observation, there are lots of facilities that are still infeasible to use. The purpose of this research is to describe and analyze Regional Regulation No. 8 of 2019 Semarang District and to obtain the resistivity factor and the driving factor faced in implementing the policy. This research uses qualitative methods. The result of this research shows that the implementation of tourism policy in Semirang Waterfall Tourist District is not enforceable yet, where the quantity and quality factors show that there has not been any increase in the number of visitors and the number of infrastructure facilities and conditions of infrastructure that are infeasible for use. In terms of tourism institutional factors, there is still a lack of human resources at the Forest Village Community (LMDH) of Gogik Village. In terms of the tourism promotion factor, there have been efforts made by LMDH in Gogik Village to promote tourism objects. In the organizational ability factors, two out of three elements are unfulfilled: the increase in service and SOP. People have yet to socialize about regional policy in the information factor, and it is still impossible to do so in the potention distribution factor.Improvements that can be given are: improving infrastructure, increasing the number of LMDH members, collaborating with other tourist attraction managers to create communication media, increasing service and SOP updates, and restructuring the organization.